Resilience (Boston, 2017)
How do some people bounce back with vigor from daily setbacks, professional crises, or even intense personal trauma? This book reveals the key traits of those who emerge stronger from challenges, helps you train your brain to withstand the stresses of daily life, and presents an approach to an effective career reboot. This volume includes the work of: Daniel Goleman Jeffrey A. Sonnenfeld Shawn Achor This collection of articles includes ?How Resilience Works,? by Diane Coutu; ?Resilience for the Rest of Us,? by Daniel Goleman; ?How to Evaluate, Manage, and Strengthen Your Resilience,? by David Kopans; ?Find the Coaching in Criticism,? by Sheila Heen and Douglas Stone; ?Firing Back: How Great Leaders Rebound After Career Disasters,? by Jeffrey A. Sonnenfeld and Andrew J. Ward; and ?Resilience Is About How You Recharge, Not How You Endure,? by Shawn Achor and Michelle Gielan. How to be human at work. The HBR Emotional Intelligence Series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.
Keywords: Resilience (Personality traits)